'Porcelain aorta': a proposed definition and classification of ascending aortic calcification. Issue 1 (26th January 2018) - Snow, Thomas; Semple, Thomas; Duncan, Alison; Barker, Sarah; Rubens, Michael; DiMario, Carlo; Davies, Simon; Moat, Neil; Nicol, Edward David
Abstract : Introduction: 'Porcelain aorta' is listed in the second consensus document of the Valve Academic Research Consortium as a risk factor in aortic valve replacement. However, the extent of circumferential involvement is poorly defined with great variability in reported incidence. We present a simple, reproducible classification to describe the extent of aortic calcification and thus appropriately define 'porcelain aorta', aiding clinical decision-making and registry data collection. Methods: 175 consecutive CT aortograms were reviewed. The aorta was divided into three sections, and each section divided into quadrants. These were individually scored using a 5-point scale (0—no calcification, 5—complete contiguous calcification). Results for each quadrant were summated for each segment to provide an indication of the distribution of calcification. Results: Only one patient (0.6%) had a 'true' porcelain aorta, defined as contiguous calcification across all quadrants at any aortic level. Intraobserver and interobserver variation was excellent for the ascending aorta (K=0.85–0.88 and 0.81–0.96, respectively) while the interobserver variation in the transverse arch was good at 0.75. Conclusions: Our data suggest the incidence of 'true' porcelain aorta may be significantly lower than reported in the literature. The predominance of calcification within the anterior wall of the proximal ascending aorta and the superior wall of the transverse arch may be clinically important. Application of this quick, simple and reproducible grading system, with no requirement for advanced software, may provide a tool to support accurate assessment of focal aortic calcification and its relationship to subsequent procedural risk.